World Trade Indicators 2008 : Benchmarking Policy and Performance - Islam, Roumeen; Zanini, Gianni (Washington, DC : World Bank, 2012)
The World Trade Indicators (WTI) database and ranking tool cover country level indicators of trade performance and policies and institutions that affect trade. The purpose of this initiative by the World Bank is to benchmark progress in these areas while highlighting important data gaps. The value of timely, good-quality data for policy making and effective international negotiations cannot be underestimated. Such data are also needed for reducing transactions costs for businesses. This publication summarizes patterns in world trade policy and trade outcomes revealed by the WTI database, focusing mainly on regional and income level variations and providing the context to help evaluate individual country progress. It is hoped that this initiative, by benchmarking country performance in various policy and outcome areas, will enhance the ability of policy makers to design and implement needed trade-related reforms. It is also hoped that countries will be further encouraged to produce better and more up to date data and make it publicly available, both domestically and in international databases, in a timely manner.